One-Pot, Optimized Microwave-Assisted Synthesis of Difunctionalized and B–N Co-Doped Carbon Dots: Structural Characterization - Hector Daniel Ibarra-Prieto; Alejandra Garcia-Garcia; Faustino Aguilera-Granja; Diana Carolina Navarro-Ibarra; Ignacio Rivero-Espejel (Nanomaterials, 2023)
In this work, we employed a novel microwave-assisted synthesis method to produce nitrogen and boron co-doped carbon dots (B–N co-doped CDs). To achieve optimal synthesis, we conducted a comprehensive parameter modulation approach, combining various synthesis temperatures, times, and precursor concentrations, while keeping the power constant at 150 W and pH 5. Using maximum fluorescence emission as our response variable, the best conditions were identified as 120 °C, 3 min, and a precursor concentration of 1 mg/mL. Characterization using field emission scanning electron microscopy revealed these CDs to have a spherical morphology with an average size of 10.9 ± 3.38 nm. Further high-resolution transmission electron microscopy showed an interplanar distance of 0.23 nm, which is in line with prior findings of CDs that present a 0.21 nm distance corresponding to the (100) plane of graphite. Optical properties were ascertained through UV–vis absorption, identifying distinct π–π* and n–π* transitions. Fluorescence spectroscopy highlighted an emission peak at 375 nm when excited at 295 nm, achieving a quantum yield of 56.7%. Fourier-transform infrared spectroscopy and Raman spectroscopy analyses confirmed the boronic acid and amine groups’ presence, underscoring the graphitic nature of the core and the co-doping of boron and nitrogen. These empirical observations were compared with theoretical investigations through simulated Raman spectra, proposing a potential structure for the CDs. X-ray photoelectron spectroscopy further endorsed the co-doping of nitrogen and boron, along with the detection of the specified functional groups. All these characteristics could lend this nanomaterial to different types of applications such as fluorescent probes for a broad range of analytes and for fluorescent cell imaging.